MicroRNA Exocytosis by Vesicle Fusion in Neuroendocrine Cells - Park, Yongsoo (Frontiers in Endocrinology, 2017)
MicroRNAs (miRNAs) are short non-coding RNAs that post-transcriptionally regulate gene expression inside the cell that transcribe them. Extracellular circulating miRNAs are also observed outside the cell, but their origin is poorly understood. Recently, miRNA has been shown to be exocytosed by vesicle fusion; this observation demonstrates that vesicle-free miRNAs are secreted from neuroendocrine cells, in a manner similar to hormone secretion. miRNAs are stored in large dense-core vesicles together with catecholamines, then released by vesicle fusion in response to stimulation; in this way vesicle-free miRNA may regulate celltocell communication including the regulation of gene expression and cellular signaling. Therefore, miRNA has been suggested to function as a hormone; i.e., a ribomone (ribonucleotide + hormone). This review focuses on the mechanisms by which vesicle-free miRNAs are secreted from neuroendocrine cells and will discuss potential functions of vesicle-free miRNAs and how vesicle-free miRNAs regulate celltocell communication.